First report of the phytoseiid mite Neoparaphytoseius charapa Jiménez, McMurtry & Moraes, 2014 (Acari: Phytoseiidae) to Brazil, with notes on the occurrence of the genus - Souza, Raimundo B.; Duque, Michele P.; Amorim, Suziane A.; Cavalcante, Ana C. C.; Guesdon, Isabel R.; Demite, Peterson R. (Entomological Communications, 2021)
Phytoseiid mites collected on Inga edulis L. (Leguminosae) in three localities in the Amazonas State, Brazil, were identified as Neoparaphytoseius charapa Jiménez, McMurtry & Moraes, 2014. This is the first report of this species in Brazil. Notes on geographic occurrence and association of Neoparaphytoseius Chant & McMurtry, 2003 species with host plants are presented.